2017
DOI: 10.1007/s10103-017-2216-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ultrafast fiber laser application on the bond strength of resin cement to titanium

Abstract: The purpose of this study was to investigate the effect of ultrafast fiber laser treatment on the bond strength between titanium and resin cement. A total of 60 pure titanium discs (15 mm × 2 mm) were divided into six test groups (n = 10) according to the surface treatment used: group (1) control, machining; group (2) grinding with a diamond bur; group (3) ultrafast fiber laser application; group (4) resorbable blast media (RBM) application; group (5) electro-erosion with copper; and group (6) sandblasting. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 39 publications
2
16
0
7
Order By: Relevance
“…26,40 Literatürde ve klinik pratiğinde çokça çalışılmış ve halen araştırılmaya devam eden en iyi en popüler teknik kumlamadır. [41][42][43][44][45] Çeşitli çalışmalar, farklı alüminyum oksit partikül boyutları ile (25-250 µm) kum-…”
Section: Tepeklinikunclassified
See 3 more Smart Citations
“…26,40 Literatürde ve klinik pratiğinde çokça çalışılmış ve halen araştırılmaya devam eden en iyi en popüler teknik kumlamadır. [41][42][43][44][45] Çeşitli çalışmalar, farklı alüminyum oksit partikül boyutları ile (25-250 µm) kum-…”
Section: Tepeklinikunclassified
“…Bazı çalışmalar, abutment yüzeylerinin 110-125 µm alüminyum oksit partikülleriyle kumlanmasının materyalin ıslanabilirliğini arttırması ve retansiyon alanları oluşturmasıyla bağlanma kuvvetini arttırdığını belirtmişlerdir. 42,46 Diğer in-vitro çalışmalar ise, 50 µm alüminyum partikülleriyle kumlamanın da bağlanma kuvvetinde etkili olduğunu bildirmişlerdir. 41,47 Titanyum yüzeylerinin alüminyum oksit partikülleri ile kumlanmasıyla elde edilen yüzey pürüzlülüğünün titanyum ile üst yapı materyali arasındaki bağlanma kuvvetini arttırdığını belirten çalışmalar olduğu gibi 6,4 kumlama sonrası incelenen metal yüzeylerinde alüminyum oksit partiküllerine ait kalıntılar görülmüştür.…”
Section: Tepeklinikunclassified
See 2 more Smart Citations
“…In the last decade, with the advancement of laser techniques, the use of lasers as an alternative pretreatment method for dental procedures has become prevalent, such as by applying laser treatment to dental materials to improve the bonding properties between materials and resin-based luting agents [24] or materials and porcelain [25]. This resulted in the attempted use of lasers as a surface treatment method for zirconia ceramics, in order to enhance the bonding strength and durability of a number of dental materials by altering the surface microstructures [26][27][28]. Some studies have reported that lasers improve the bond strengths of zirconia ceramics and other substrate materials; however, other studies have shown contradictory results [29][30][31].…”
Section: Introductionmentioning
confidence: 99%